Immediate post-exercise blood pressure and arterial compliance in middle-aged and older normotensive females: A cross-sectional study - Eduardo C. Costa (Nature Portfolio, 2020)
Abstract This study examined whether immediate post-exercise systolic blood pressure (SBP) is associated with arterial compliance in middle-aged and older normotensive females. A total of 548 normotensive, non-frail females aged 55 years and older with no previous history of cardiovascular disease (CVD) participated in this cross-sectional study. Large and small arterial compliance were assessed by pulse wave analysis. Reduced arterial compliance was defined based on age and sex cutoffs. SBP was measured at rest and immediately following a 3-min moderate step-test. CVD risk factors were also assessed (e.g. resting systolic and diastolic BP, fasting glucose, triglycerides, cholesterol, body mass index). A total of 15.1% and 44.0% of the participants showed reduced large and small artery compliance, respectively. Immediate post-exercise SBP was associated with reduced large (OR 1.02 per 1 mmHg increase in post-exercise SBP, 95%CI 1.01–1.04; p = 0.010) and small (OR 1.02 per 1 mmHg increase in post-exercise SBP, 95%CI 1.00–1.03; p = 0.008) arterial compliance. Participants with highest immediate post-exercise SBP (quartile 4; i.e. ≥ 165 mmHg) showed increased odds ratios for reduced large (2.67, 95%CI 1.03–6.94; p = 0.043) and small (2.27, 95%CI 1.22–4.21; p = 0.010) arterial compliance compared to those with the lowest immediate post-exercise SBP (quartile 1; i.e. ≤ 140 mmHg), independent of other established CVD risk factors. Immediate post-exercise SBP following a brief moderate step-test seems to be able to discriminate reduced arterial compliance in middle-aged and older normotensive females.